Transition-Metal Catalysis and Organocatalysis: Where Can Progress Be Expected? - Zhou, Qi-Lin (Angewandte Chemie International Edition, 2016)
“… Most transition‐metal catalysts and organocatalysts do not meet the requirements for modern industrial manufacturing processes. Their main limitation is low efficiency. The need to develop highly efficient catalysts and related catalytic reactions is a never‐ending challenge in synthetic chemistry …” Read more in the Editorial by Qi‐Lin Zhou.